Permanent visitors - Moffett, Kevin, 1972- (John Simmons short fiction award., 2006)
Settled amid the seasonal amusements and condominium-lined beaches of the Florida coast, the characters who inhabit Kevin Moffett's award-winning stories reach out of their lives to find that something unexpected and mysterious has replaced what used to be familiar. Some are stalled in the present, alone or lonely, bemused by mortality and disappointment. Some move toward the future heartened by what they learn from those around them--a tattoo artist, an invented medicine man, zoo animals, strangers, fellow outsiders. Deftly rendered, these stories abound with oddness and grace. In "Tatt